Mechatronics and Machine Vision in Practice 3 (Springer International Publishing, 2018)
In contrast with previous books on mechatronics and machine vision in practice, a significant number of chapters focus on systems designed for human interaction and deciphering human motion. Examples illustrate assistive actuation of hip joints, the augmentation of touch sense in artificial hand prostheses and helping stroke survivors in repetitive motion therapy. Interactive mechatronics and the experience of developing machine interfaces has enabled an examination of how we use mechatronics in the service of training, and even to consider why computer games perhaps appear to capture attention so much more readily than a human instructor! Mechatronics continues to be an exciting and developing field. It is now an essential part of our world and living experience. This and the previous books in this series illustrate the journey in developing the use of mechatronics so far. We anticipate that you will find the chapters here an equal source of inspiration for new devices to solve the challenges of new applications, and of course as a resource for teaching and inspiring the new generation of mechatronics engineers. .